2022
DOI: 10.20944/preprints202205.0307.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simulating 3D Human Postural Stabilization in Vibration and Dynamic Driving

Abstract: In future automated vehicles we will often engage in non-driving tasks and will not watch the road. This will affect postural stabilization and may elicit discomfort or even motion sickness in dynamic driving. Future vehicles shall accommodate this by properly designed seats and interiors whereas comfortable vehicle motion shall be achieved with smooth driving styles and well de-signed (active) suspensions. To support research and development in dynamic comfort, this paper presents validation of a multi-segmen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…An exposure of 60 seconds per motion condition as in Mansfield et al (2006) was found sufficient to obtain coherent and consistent results from 0.34 Hz. Results below this frequency, as well as the significant effects of amplitude, will be evaluated in the time domain using 3D nonlinear models of human seat interaction (Mirakhorlo, Kluft, Irmak, Shyrokau and Happee, 2021). Such biomechanical models can also address cross-axis nonlinearity as demonstrated by Zheng, Qiu and Griffin (2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An exposure of 60 seconds per motion condition as in Mansfield et al (2006) was found sufficient to obtain coherent and consistent results from 0.34 Hz. Results below this frequency, as well as the significant effects of amplitude, will be evaluated in the time domain using 3D nonlinear models of human seat interaction (Mirakhorlo, Kluft, Irmak, Shyrokau and Happee, 2021). Such biomechanical models can also address cross-axis nonlinearity as demonstrated by Zheng, Qiu and Griffin (2019).…”
Section: Discussionmentioning
confidence: 99%
“…Future research shall explore contributions of translational and rotational motion to comfort perception in particular for the head. To achieve this we are currently integrating models of sensory integration (Oman, 1982) and postural stabilization (Happee, de Bruijn, Forbes and van der Helm, 2017) in full body biomechanical models (Mirakhorlo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%